PSME2 identifies immune-hot tumors in breast cancer and associates with well therapeutic response to immunotherapy - Wu, Cen; Zhong, Ren; Sun, Xiaofei; Shi, Jiajie (Frontiers in Genetics, 2022)
Breast cancer (BrCa) is a heterogeneous disease, which leads to unsatisfactory prognosis in females worldwide. Previous studies have proved that tumor immune microenvironment (TIME) plays crucial roles in oncogenesis, progression, and therapeutic resistance in BrCa. However, biomarkers related to TIME features have not been fully discovered. Proteasome activator complex subunit 2 (PSME2) is a member of proteasome activator subunit gene family, which is critical to protein degradation mediated by the proteasome. In the current research, we comprehensively analyzed the expression and immuno-correlations of PSME2 in BrCa. PSME2 was significantly upregulated in tumor tissues but associated with well prognosis. In addition, PSME2 was overexpressed in HER2-positive BrCa but not related to other clinicopathological features. Interestingly, PSME2 was positively related to immune-related processes and identified immuno-hot TIME in BrCa. Specifically, PSME2 was positively correlated with immunomodulators, tumor-infiltrating immune cells (TIICs), immune checkpoints, and tumor mutation burden (TMB) levels. Moreover, the positive correlation between PSME2 and PD-L1 expression was confirmed in a tumor microassay (TMA) cohort. Furthermore, in an immunotherapy cohort of BrCa, patients with pathological complete response (pCR) expressed higher PSME2 compared with those with non-pCR. In conclusion, PSME2 is upregulated in tumor tissues and correlated with the immuno-hot TIME, which can be a novel biomarker for the recognition of TIME features and immunotherapeutic response in BrCa.